Comparison effects of probiotics, sesame seeds, and wheat supplementation on reproductive performance of giant freshwater prawns (Macrobrachium rosenbergii) - Alansyah, Ikhsan Bayu; Farastuti, Eko Rini; Mulyana, (JURNAL MINA SAINS, 2026)
The culture of giant freshwater prawn (Macrobrachium rosenbergii) has promising economic prospects; however, it faces constraints in reproduction, particularly the slow process of gonadal maturation, which depends on seasonal factors. This dependency results in limited availability of mature broodstock throughout the year. The objective of this study was to evaluate the effects of dietary supplementation with probiotics, wheat, and sesame seeds on the reproductive performance of giant freshwater prawn. The research was conducted at Djuanda University, Bogor, West Java. The experiment was carried out from July to September 2024. The experimental design consisted of four treatments with four replications over a 70-day period: P1 (control), P2 (feed + probiotic), P3 (feed + probiotic + wheat), and P4 (feed + probiotic + sesame seeds). The observed parameters included body weight, body length, cephalothorax circumference, gonadal maturation stage (GMS), and gonadosomatic index (GSI). The results showed that treatment P4 produced a significant increase in all parameters, with a final body weight of 20±0.92 g, body length of 18.45±0.95 cm, cephalothorax circumference of 8.14±0.84 cm, and the highest GSI of 2.33%. The highest gonadal maturation stage (GMS IV) was also achieved more rapidly in P4 compared to other treatments. These findings indicate that the combination of probiotics and sesame seeds is effective in accelerating gonadal maturation and enhancing reproductive performance. Therefore, the use of natural additives such as probiotics and sesame seeds has potential as an alternative technology to improve the productivity of giant freshwater prawn culture.